2008
DOI: 10.1157/13127042
|View full text |Cite
|
Sign up to set email alerts
|

Equivalence of a single saline nebulised dose of formoterol powder vs three doses of nebulised Albuterol every twenty minutes in acute asthma in children: a suitable cost effective approach for developing nations

Abstract: Single dose nebulised Formoterol Fumarate (dry powder) in sterile saline solution, as depicted in this trial, is equivalent to three doses of Albuterol every twenty minutes for one hour in acute asthma in children, simplifying acute care management and at one fifth of medication costs. A pursuit of simpler and more cost effective approaches is found wanting in developing nations with depressed economies and unique cultural and socio-medical contexts; also, in countries where pharmaco-economics orients quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…Children received either single dose of 25 μg formoterol fumarate by nebuliser or 3 doses of Salbutamol (Albuterol) every twenty minutes for one hour by nebuliser. Symptoms score, oxygen saturation and lung function testing recorded before and one hour after commencing treatment showed significant improvement [7]. The results of our study are in concordance with these studies even though we enrolled children with mild exacerbations and used single dose of either medication delivered by MDI and spacer.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Children received either single dose of 25 μg formoterol fumarate by nebuliser or 3 doses of Salbutamol (Albuterol) every twenty minutes for one hour by nebuliser. Symptoms score, oxygen saturation and lung function testing recorded before and one hour after commencing treatment showed significant improvement [7]. The results of our study are in concordance with these studies even though we enrolled children with mild exacerbations and used single dose of either medication delivered by MDI and spacer.…”
Section: Discussionsupporting
confidence: 85%
“…There are few studies in children [6,7] which have compared formoterol and salbutamol delivered by different routes like nebulisation or dry powder inhalation in acute exacerbation. These studies concluded that both the drugs were equally efficacious in acute exacerbation.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the 18 studies included originated from the United States, followed by the UK, Colombia, the Netherlands, Canada, Germany, Hong Kong, and Venezuela (Appendix ).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies assessed a mixed population, although only the results restricted to pediatric patients were considered. The asthma type and severity of the included studies differed, including allergic, persistent, acute, and chronic asthma.…”
Section: Resultsmentioning
confidence: 99%
“…There is a paucity of published data, particularly from randomized controlled studies, evaluating the safety of LABA use in children with acute bronchoconstriction 4, 5, 9–11. LABAs, like arformoterol, that result in rapid onset of bronchodilation and which are nebulized, may have the potential to be used off‐label in the treatment of acute bronchoconstriction in children with asthma.…”
Section: Discussionmentioning
confidence: 99%